(untitled) (SAARC Journal of Agriculture, 2023)
This research was taken to improve the performance of native duck. Two native duck varieties, Rupali and Nageswari of 6th generation were selected aiming to increase their laying performances. A total of 540 ducklings of both genotypes were hatched and brooded in brooder house. Male and female ducks were separated and marked with wing band at 12 weeks of age. At 40 weeks of age, a total of 300 ducks of both genotype were selected on the basis of selection index comprising the parameters of age at first egg, body weight at first egg, egg production % and egg weight. The individual with the higher total score was selected for breeding purposes. Selected male and female ratio were 1:5 using natural mating. The selection intensity and expected selection responses of selection criteria of two duck genotypes were estimated. Selection responses for ASM (day), egg weight (g) and egg production rate was -1.84, 1.08 g and 0.45 in case of Rupali and -1.66, 1.35 and 0.73 for Nageswari, respectively. Egg production % was numerically higher in Rupali (60.12%) than Nageswari (58.41%). Egg weight (EW) and feed intake were significantly differences between two native ducks where both higher values were found in Rupali (EW 64.83g and feed intake 134g) than Nageswary. Egg shape index was significantly higher in Rupali (76%) than Nageswari (75%) duck. In conclusion, Rupali ducks showed better production performance and it is suggested that selective breeding of duck may have significant impact on the development of native duck. SAARC J. Agric., 21(1): 253-263 (2023)